2015
DOI: 10.1016/j.immuni.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

A Wave of Regulatory T Cells into Neonatal Skin Mediates Tolerance to Commensal Microbes

Abstract: Summary The skin is a site of constant dialogue between the immune system and commensal bacteria. However, the molecular mechanisms that allow us to tolerate the presence of skin commensals without eliciting destructive inflammation are unknown. Using a model system to study the antigen-specific response to S. epidermidis, we demonstrated that skin colonization during a defined period of neonatal life was required to establish immune tolerance to commensal microbes. This crucial window was characterized by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
436
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(454 citation statements)
references
References 58 publications
13
436
0
5
Order By: Relevance
“…Nevertheless, a previous study showed that extracellular products of S. epidermidis promoted the suppressive activity of human Tregs (47), further indicating that this cell population may be involved in counterinflammatory mechanisms operating during infections with this bacterium. Tregs were recently shown to be crucial for establishing S. epidermidis skin commensalism (48). Taking our results into account, it will also be interesting to ascertain in future studies whether Tregs may contribute to the persistence of biofilm-related S. epidermidis infections (49).…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, a previous study showed that extracellular products of S. epidermidis promoted the suppressive activity of human Tregs (47), further indicating that this cell population may be involved in counterinflammatory mechanisms operating during infections with this bacterium. Tregs were recently shown to be crucial for establishing S. epidermidis skin commensalism (48). Taking our results into account, it will also be interesting to ascertain in future studies whether Tregs may contribute to the persistence of biofilm-related S. epidermidis infections (49).…”
Section: Discussionmentioning
confidence: 65%
“…Although little is understood about the factors that regulate the acquisition of skin microbes at birth, regulatory T cells, which are highly enriched in the skin tissue, have been proposed to control early dialogue with the microbiota. Indeed, colonization of mouse skin with S. epidermidis early in life (but not later) induces tolerance to the same microbe in adulthood 61 and promotes accumulation of S. epidermidis -specific regulatory T cells in neonatal skin 62 .…”
Section: Host–mutualist Interactionsmentioning
confidence: 99%
“…For example, of the CD4 + T cells present in the gastrointestinal tract of adult mice, 10% to 20% are Tregs (24), compared with 20% to 60% in skin. The majority of Tregs found in the GI tract are peripheral Tregs induced by commensal microbes, compared with Tregs in mouse skin, which appear to be thymus-derived and accumulate in the skin during a specific window of neonatal development (25).…”
Section: Cd8mentioning
confidence: 99%